Training and Detraining Effects on Functional Fitness after a Multicomponent Training in Older Women - Maria Carvalho (2009)
Background. Several studies have been carried out in order to evaluate the potential influence of increased physical activity on the health, biological ageing and functional ability of the elderly. However, only limited information is available on the effects of multicomponent training and detraining on functional performance. Objective: The purpose of the present study was to investigate the effect of 8-month multicomponent training and 3-month detraining on the functional fitness of older women. Methods: Fifty-seven women were randomly assigned to an exercise (n = 32; 68.4 +/- 2.93 years) or a control group (n = 25; 69.6 +/- 4.20 years). The training program consisted of 2 sessions per week of aerobic,strength, balance and flexibility exercises. The functional fitness test battery was performed to assess the physical parameters associated with independent functioning in older adults. Results: No significant changes were observed in bodymass index and cardiovascular endurance as a result of the exercise training. Training induced significant (p < 0.05) improvements in chair stand (27.3%), arm curl (17.4%), chair sit-and-reach (17.4%), up-and-go (11%) and back scratch (14.5%) tests. However, both upper and lower body strength and upper and lower flexibility declined significantly after detraining in the exercise group. Conclusion: The results of this study highlight the negative effects of interrupting exercise on several physical parameters of functional fitness. Copyright (c) 2008 S. Karger AG, Basel